Polish Gymnastic Society "Sokół" in the Province of Ternopil in the Years 1920-1939 - Teresa Drozdek-Małolepsza; Eligiusz Małolepszy (Jan Długosz University in Częstochowa, 2024)
The purpose of this article is to present the activities of the Polish Gymnastic Society "Sokół" in the Province of Ternopil in the years1920-1939. In the interwar period, the "Sokół" nests in the Province of Ternopil were part of the Lesser Poland (Małopolska) Region. In the 1920s and early 1930s, several "Sokół" regions operated in the Province of Ternopil: Brody, Brzeżany, Buczacz, Czortków, Ternopil, and Złoczów. In the 1930s, the Ternopil region functioned, while some nests were part of the Lviv region. "Sokół" nests participated in work on shaping the infrastructure needed for their activities, including the construction of "Sokół" buildings and facilities for physical activity and military training. Sokół members took part in physical education courses. "Sokół" was active in the field of physical education, sports, and military training. In sports activities, they engaged in gymnastics, athletics, sports games, shooting, water sports, winter sports, and marching competitions. Educational, patriotic, cultural and educative activities were important in the work of "Sokół," including the celebration of national anniversaries, academies, and evening gatheringsdedicated to Tadeusz Kościuszko, the patron of Polish Sokolism.